Accidentes laborales en el Hospital Clínico Universidad de Chile en el período 2003 - 2008 - Rojas V., Nicolás; Seymour M., Camila; Suárez S., Rodrigo; Torres A., Pedro (Revista Hospital Clínico Universidad de Chile, 2009)
Workers in the health area are constantly exponed to occupational risk factors that can lead to labourable accidents. The aim of this work is to name the accidents within the Clinical Hospital of the Universidad de Chile and other centers dependent on this, during the period between the years 2003 and 2008. In the year 2005,a descriptive study was made, which showed a higher rate of incidence in laboural accidents (8,48 x 100). Female accidents presented a higher rate of incidence and the highest rate of accidents was among the ages 31 to 40 years old. The most frequent type of accidents corresponds to cutting and stabbing injuries. On the other hand, the hit with an object was the most frequent kind of attack in the accidents with 24.8%. The technician group accidents corresponded to 2.2%. The results obtained are partially similar to other hospital Centers. It would be important to consider a risk prevention programespecially oriented to the technician group as more than the half of the labour accidents belong to this labour group.